Multiple Molecular Targets Associated with Genomic Instability in Lung Cancer - Giovanny Soca-Chafre; Angelica Montiel-Dávalos; Inti Alberto De La Rosa-Velázquez; Claudia Haydeé Saraí Caro-Sánchez; Adriana Peña-Nieves; Oscar Arrieta (International Journal of Genomics)
Lung cancer (LC) is the first cause of cancer-related deaths worldwide. Elucidating the pathogenesis of LC will give information on key elements of tumor initiation and development while helping to design novel targeted therapies. LC is an heterogeneous disease that has the second highest mutation rate surpassed only by melanoma, since 90% of LC occurs in tobacco smokers. However, only a small percent of smokers develops LC, indicating an inherent genomic instability. Additionally, LC in never smokers suggests other molecular mechanisms not causally linked to tobacco carcinogens. This review presents a current outlook of the connection between LC and genomic instability at the molecular and clinical level summarizing its implications for diagnosis, therapy, and prognosis. The genomic landscape of LC shows widespread alterations such as DNA methylation, point mutations, copy number variation, chromosomal translocations, and aneuploidy. Genome maintenance mechanisms including cell cycle control, DNA repair, and mitotic checkpoints open a window to translational research for finding novel diagnostic biomarkers and targeted therapies in LC.